Pendampingan Manajemen Pemasaran pada Industri Olahan Pertanian di Mojokerto - Dana Marsetiya Utama; Teguh Baroto; Arnelia Dwi Yasa (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
The "Ria" home industry has experienced many problems in the production and management processes. In the production process, it has limitations in packaging. In addition, the business financial management aspect is still mixed with household finances. Marketing is done traditionally and has not been effective. This PKM program aims to provide assistance in packaging production tools, provide training related to marketing management and product packaging. The method of activities carried out is Focus Group Discussion (FGD) and Participatory Rural Appraisal (PRA) involving partners. The results of this PKM show that the production packaging process runs smoothly with the presence of a modern sealer, participants' knowledge of the Marketing Mix increases, product marketing is carried out offline and online.